Bolt Preload Measurements Using Ultrasonic Methods - Notch, James S. (Engineering Journal, 1985)
Significant research efforts and technological advances have occurred over the past years with regard to the design of high-strength bolted connections. The development of quality assurance programs aimed at evaluating whether sufficient bolt pre-tension has been achieved during field bolt-up is equally important. A high-strength bolted connections superior strength characteristics are based on the development of frictional forces between the clamped plates or members. High-strength bolts are not, as in the eyes of many laymen, merely "bearing type" pins holding the joint together—they are fasteners which must achieve sufficient pre-tension to clamp the connection plies together and thereby provide adequate slip resistance. The importance of developing sufficient clamping force is even more important with todays prevalent use of oversize and slotted holes. In addition to direct tension indicator devices which have shown merit, the most common recognized method of bolt tightening is the turn-of-the-nut method. Based primarily on strain control, the method relies on a specified incremental turn to elongate the bolt. Although simple in concept, the method is difficult to control under field conditions. The greatest variables are the definitions of "snug tight," the starting point for the incremental turn, and the accuracy of the rotational measurements.